Prenatal and perinatal risk factors for allergic diseases development - Filipovic, Ivana (Halo 194 Scientific Journal of Emergency Medicine, 2022)
Three components are necessary for the development of allergic diseases: heredity, contact with the allergen and environmental factors. Allergic diseases are the most common chronic diseases in children and adolescents. The aim of this paper is to point out the latest findings on prenatal and perinatal risk factors for the development of atopic diseases. The research was conducted by searching papers in the MEDLINE and PubMed databases in the period up to September 2021. The mother's immune system during pregnancy plays a key role in the development of the fetus, and it certainly affects the overall well-being of her casino offspring in life. Immune dysregulation during the gestation period has been shown to be associated with adverse maternal, fetal, and neonatal outcomes. Contrary to the long-established view of amniotic fluid as a sterile, it is now known that the fetus receives its first dose of probiotics by swallowing amniotic fluid.
Keywords: Prenatal factors; perinatal factors; allergic diseases